The Development of "Macromedia Flash" Interactive Media For Subject Matter of Nature and Changes In The Subjects of Science For Students of Fourth Graders At Primary School 4 Selong - Sururuddin, Muhammad; Parhanuddin, Lalu; Mispandi, Mispandi (IJE : Interdisciplinary Journal of Education, 2024)
This study aims to produce interactive learning media using "Macromedia Flash" on the subject matter of the nature and changes in the shape of objects. The subjects were students of fourth graders of elementary school. Data collection instruments included validation sheets, achievement test, and student response questionnaire. The data analysis technique was a calculation using a five scale for analyzing the results of the validation and scoring of values ​​(1) and no value (0) for student questionnaire responses. The results of validation from media experts showed good qualifications and the results of validation from material experts showed good qualifications as well with the total score for media experts was 61 with an average of 4.0 while the value of material experts amounted to 58 with an average of 3.8. The results of the questionnaire responses of students in the field test total overall value of 173 with a percentage of 91.0%. The value was conversion table which the response of students was to the media included in both categories. The number of students who completed was 16 out of 19 students, and the highest number was 90 and the lowest score was 55 with KKM 70, so the percentage of student’s completeness learning classically was 84.20%.